GRAMMAR AS COMMUNICATION: A DISCOURSE GRAMMAR OF DEIXIS - Drissia Chouit (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
This research article examines the micro-system THIS/THAT in contemporary English within the theoretical framework of Metaoperational Grammar. It proposes a new approach to bring into light how this pair functions, giving due account to the importance of the context and the communication goals that determine the selection of one of these operators in a given communication act. It aims, therefore, to bridge the gap between "grammar" and "communication" and to show that grammatical operators are at the heart of communication strategies and semantic interpretation. These insights into the functioning of THIS and THAT present, in fact, one of my main contributions to modern linguistics. Metaoperational Grammar has provided me with theoretical tools to (1) show the limitations of descriptive approaches which base their explanation of this pair on the proximal/non-proximal distinction; (2) bring into light the abstract mechanisms underlying the processing of these operators; and (3) show the role played by grammatical operators in building semantic interpretation and revealing the communication strategies of the speaker. Based on authentic examples, this article shows that the spatial-temporal parameters of proximity to the speaker (THIS) and distance from the speaker (THAT) are not endowed with explanatory power to account for the emergence of these operators in discourse, and hence the need for a discourse grammar of deixis.